The Effectiveness of The Battle Math Educational Game to Improve Motivation And Numeracy Skills Of Fourth Grade Students - Julaikum, Er; Khatimah, Husnul; Kurniawan, Edy (Journal of Educational Sciences, 2025)
The latest results from PISA 2022 and the National Assessment show that Indonesian primary school students’ numeracy proficiency remains weak, with most exhibiting low learning motivation and lacking media to support interactive learning. This study examined the role of the Battle Math educational game in improving learning motivation and numeracy skills of fourth-grade students at SDN 71 Wenggo, Bima City. A quasi-experimental one-group pretest–posttest design was applied, involving eight students over four game-based learning sessions. Data were collected using a numeracy test and a motivation questionnaire based on the ARCS model. The Wilcoxon Signed Rank Test revealed that the mean motivation score increased significantly from 41.13 to 88.00 (p = 0.012) after the intervention. The Battle Math educational game appears to bridge the gap between what students are expected to learn and what they can meaningfully apply. Integrating such game-based media is recommended as a pragmatic and scalable approach to improving early mathematics learning, particularly in under-resourced elementary schools.